Cycling performance decrement is greater in hypobaric versus normobaric hypoxia - Beidleman, B. A.; Fulco, C. S.; Staab, J. E.; Andrew, S. P.; Muza, S. R. (Extreme Physiology & Medicine, 2014)
Background: The purpose of this study was to determine whether cycling time trial (TT) performance differs between hypobaric hypoxia (HH) and normobaric hypoxia (NH) at the same ambient PO2 (93 mmHg, 4,300-m altitude equivalent). Methods: Two groups of healthy fit men were matched on physical performance and demographic characteristics and completed a 720-kJ time trial on a cycle ergometer at sea level (SL) and following approximately 2 h of resting exposure to either HH (n=6, 20±2 years, 75.2±11.8 kg, mean±SD) or NH (n=6, 21±3 years, 77.4±8.8 kg). Volunteers were free to manually increase or decrease the work rate on the cycle ergometer. Heart rate (HR), arterial oxygen saturation (SaO2), and rating of perceived exertion (RPE) were collected every 5 min during the TT, and the mean was calculated. Results